2009
DOI: 10.1089/pho.2007.2222
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Laser Therapy in Subacromial Impingement Syndrome

Abstract: Our study was unable to demonstrate any distinct advantage of low-level laser therapy over exercise alone. Comprehensive home exercise programs should be the primary therapeutic option in the rehabilitation process in SIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
3
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 20 publications
0
52
3
1
Order By: Relevance
“…Of the three that did not, one study (Walther et al, 2004) subsequently demonstrated clinically significant changes by 12 weeks but the other two (Giombini et al, 2006;Calis et al, 2011) did not follow-up to this time point. At and beyond the 12-week follow-up point, seven of eight studies (Walther et al, 2004;Bal et al, 2009;Engebretsen et al, 2009Engebretsen et al, , 2011Østerås et al, 2009Yiasemides et al, 2011;Kromer et al, 2013;Littlewood et al, 2014a) reported clinically significant changes with a general trend towards greater change over time.…”
Section: Outcome Measures and Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the three that did not, one study (Walther et al, 2004) subsequently demonstrated clinically significant changes by 12 weeks but the other two (Giombini et al, 2006;Calis et al, 2011) did not follow-up to this time point. At and beyond the 12-week follow-up point, seven of eight studies (Walther et al, 2004;Bal et al, 2009;Engebretsen et al, 2009Engebretsen et al, , 2011Østerås et al, 2009Yiasemides et al, 2011;Kromer et al, 2013;Littlewood et al, 2014a) reported clinically significant changes with a general trend towards greater change over time.…”
Section: Outcome Measures and Outcomesmentioning
confidence: 99%
“…Six studies reported the Shoulder Pain and Disability Index (SPADI) (Kachingwe et al, 2008;Bal et al, 2009;Engebretsen et al, 2009Engebretsen et al, , 2011Yiasemides et al, 2011;Kromer et al, 2013;Littlewood et al, 2014a), three 1 Shoulder pain or shoulder impingement* or shoulder tend* or shoulder burs* or rotator cuff* or subacromial impingement* or subacromial burs* or supraspinatus* or impingement* or contractile dysfunction or painful arc* Title and abstract 2 Exercise* or eccentric* or concentric* or loaded* or resistance* or muscle* or physiotherapy* or physical therapy* or rehabilitation* or conservative management Title and abstract 3 Randomized controlled* or randomized controlled* or controlled clinical trial or randomized or placebo or randomly or trial or groups Title and abstract 4 1 and 2 and 3 …”
Section: Outcome Measures and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mann-Whitney U test for independent samples was used to compare the groups. Wilcoxon signed- 0.700 40 [20,60] 40 [15,60] 0.976 50 [25,60] 50 [20,60] 0.973 40 [20,80] 40 [20,80] 0 …”
Section: Materıal and Methodsmentioning
confidence: 99%
“…Both groups showed significant improvements; however, there were no significant intergroup differences regarding pain, functional assessment, and disability after the treatment . Bal et al (20) compared LLLT (904 nm, 5500 Hz, GaAs diode laser) and a home exercise program with a home exercise program alone. The exercise program included a pendulum exercise, a passive shoulder self-stretching exercise, isometrics, elastic band (Thera-Band®) exercises, strengthening exercises for scapular stabilizers, and advanced muscle strengthening exercises with dumbbells in a progressive manner.…”
Section: Dıscussıonmentioning
confidence: 99%